The Effect of Maleic Anhydride Concentration on Water Resistance of Carrageenan-Based Bioplastic Made using The Sol-Gel Method - Aminu, November Rianto; Setyaji, Dimas Nugraha; Hartini, Sri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
There is an increasing rate of land conversion in Indonesia that can threaten food self-sufficiency. Therefore farmers and the government must expand agriculture by developing agriculture on potential available lands such as drylands. However, drylands in Indonesia have low productivity due to low water and nutrient availability. This article aims to determine the potential use of arbuscular mycorrhizal fungi to overcome drought stress and low nutrient availability in drylands. The method used in writing this article is a desk literature study conducted by collecting data from various sources, such as scientific journals, seminar proceedings, and online reports available in related government office in West Nusatenggara Province. The data obtained were then analyzed qualitatively by identifying, reviewing, and synthesizing information to produce a complete and comprehensive explanation. The results of the literature study showed that arbuscular mycorrhizal fungi have the potential to overcome drought stress and low nutrient availability in drylands. The use of arbuscular mycorrhizal fungi can be a sustainable solution to increase agricultural productivity in drylands.